Comparative characterization Ukrainian and Russian folk riddles (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
In an article comparative aspect analyses Ukrainian and Russian folk riddles, characterized their themed art-shaped features? Indentified their differences and similarities.
Keywords: folklore; genre; shaped structure; riddle